Long-term dual-trajectories of TyG and LAP and their association with cardiometabolic multimorbidity in midlife: the CARDIA study - Lingqu Zhou; Junjie Wang; Zirui Zhou; Liangjiao Wang; Qi Guo; Hui Zeng; Ziyue Zhong; Yinyin Zhang (Cardiovascular Diabetology)
Abstract Background Insulin resistance and central obesity are major risk factors for cardiometabolic diseases. The triglyceride-glucose index (TyG) and lipid accumulation product (LAP) are markers that independently predict cardiometabolic risk. However, their combined long-term trajectories and impact on cardiometabolic multimorbidity (CMM) development remain unclear. Methods This cohort study utilized data from the Coronary Artery Risk Development in Young Adults (CARDIA) study, which tracked 3467 participants at baseline. Dual-trajectory of TyG and LAP were identified using a group-based dual-trajectory model. Cox proportional hazards models were employed to assess the relationships between dual-trajectory groups and primary cardiometabolic outcomes, including first cardiometabolic disease (FCMD), CMM (two or more conditions such as type 2 diabetes, coronary heart disease, or stroke), and all-cause mortality. Multi-state models were performed to assess the associations of dual-trajectory with CMM development. Results The study included 3467 participants with a mean age of 25.08 years (SD = 3.59). Of these, 43.4% (n = 1505) were male, and 53.2% (n = 1561) were White. Three distinct dual-trajectory groups were identified: low-increasing (61.5%), high-amplitude fluctuation (7.6%), and high-increasing (30.9%). After multivariate adjustment, compared with the low-increasing group, the high-amplitude fluctuation group exhibited significantly higher risks for FCMD (hazard ratio [HR] 1.38, 95% confidence interval [CI]: 1.08–1.77), CMM (HR 2.63, 95% CI 1.21–5.71), and all-cause mortality (HR 2.16, 95% CI 1.30–3.56), as well as elevated risks for transitions from baseline to FCMD (HR 1.41, 95% CI 1.17–1.63), FCMD to CMM (HR 2.07, 95% CI 1.53–3.96), CMM to death (HR 2.87, 95% CI 1.19–7.62). The high-increasing group showed similar results. Conclusions Elevated and fluctuating trajectories of TyG and LAP from early adulthood are associated with increased risks of CMM development in midlife. Graphical abstract